Effect of Lupinus albus Conglutin Gamma Protein on Experimentally Induced Diabetes in Rats - Bhieldeen, Marwa N.; Moustafa, Yasser M.; Tawfik, Afaf A.; Elsayed, Sami M.; El-shaarawy, Fatma F. (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Early insulin resistance and a progressive loss of pancreatic β cell function combine to cause type 2 diabetes (T2D), which leads to insufficient insulin production followed by hyperglycemia. Purified from Lupinus albus seed, conglutin gamma (Cγ) is a protein that lowers blood sugar. The primary function of adipocytokines, hormones released by adipose tissue, is to alert important organs to maintain metabolic balance. AIM: This study aimed to identify and compare the role of Cγ and glimepiride in controlling hyperglycemia, insulin secretion, insulin resistance, and hyperlipidemia in high-fat diet (HFD) and low-dose streptozotocin (STZ) induced diabetes in experimental rats. METHODS: Male Sprague–Dawley rat groups were divided into seven groups; normal, Cγ control, T2D control, and four T2D groups which received Cγ (30, 60, and 120 mg/kg) and Glimepiride (0.1 mg/kg) treatments. RESULTS: Administration of Cγ successfully eliminated hyperglycemia and increased insulin secretion and sensitivity. In addition, when compared to (STZ+HFD) control rats, treatment with Cγ improved the expression of leptin, adiponectin, and their blood concentrations, as well as the activity of the enzyme chitotriosidase. It also significantly decreased the expression of apelin, nicotinamide phosphoribosyltransferase and RBP4. CONCLUSION: The present data suggests that Cγ has an effective role in controlling hyperglycemia induced by diabetes through amelioration of leptin, adiponectin, lipid profile, and metabolic syndrome.